The Case of the Lamp That Went Out - Groner, Auguste, 1850-1929; Colbron, Grace Isabel, 1869-1943 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Case of the Lamp That Went Out" by Auguste Groner is a mystery novel likely written during the late 19th century. The story revolves around Joseph Muller, an unassuming yet brilliant secret service detective of the Imperial Austrian police, who possesses a keen instinct for solving crimes. As he navigates a case involving a murdered man found in a quiet street, the narrative unfolds with a series of intricate clues and the challenges Muller faces both from the bureaucracy of his job and the moral dilemmas embedded in his investigation. The opening of the novel introduces readers to the serene setting of a Vienna morning, quickly disrupted by the shocking discovery of a corpse by a milk girl named Anna. The body is identified as a well-dressed man with signs of foul play, prompting the arrival of police, including Muller. As Muller investigates the scene, he meticulously examines the corpse and surroundings, uncovering items that may help unravel the murder's motives. His thoughtful observations and unique character traits, including a blend of humility and brilliance, set the tone for a richly woven mystery. The contrast between the calm of the suburban setting and the dark undercurrents of the crime creates an engaging atmosphere, pulling readers into a world of intrigue and suspense. (This is an automatically generated summary.)
In Joe Muller: Detective, Being the Account of Some Adventures in the Professional Experience of a Member of the Imperial Austrian Police
Release date is 1999-07-01
Produced by An Anonymous Project Gutenberg Volunteer, and David Widger
Keywords: Fiction; Detective and mystery stories